PENGARUH LATIHAN RUBBER CORD ELBOW CURL TERHADAP KEKUATAN OTOT LENGAN DAN BAHU EKSTRAKURIKULER VOLI PADA SISWA PUTRA SMP TELEKOMUNIKASI PEKANBARU - Fadil Raflisah Yandra Raflisah Yandra; Ramadi Ramadi '; Ardiah Juita Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: this research aimed to find out the effect of rubber cord elbow training to the strength of shoulder and arm muscles in volleyball extracurricular of male students of SMP Telekomunikasi Pekanbaru, so that the students be able to make an under service so the ball could reach the opponent area. The population of this experimental research was the male players of volleyball club of SMP Telekomunikasi Pekanbaru. The total number of the active players that joined the training was 10 players. The writer used Total Sampling technique to take the sample where this sampling takes all of the population as the sample (Sugiono, 2008: 124). The instrument of this research was Expanding Dynamometer, it was aimed to measure the strength of shoulder and arm muscles. Next, the data was processed using statistics, and the writer also used the level of significance 0,05 α to test the normality by using lilifurs-test. Therefore, the alternative hypothesis was an effect of rubber cord elbow training to the strength of shoulder and arm muscles in volleyball extracurricular of male students of SMP Telekomunikasi Pekanbaru. After being analyzed using t-test formula, the value of tobserve was 14.07 and the value of ttabel was 1.812, so Tobserve>Ttabel. Based on the data analysis, the average of pre-test was 14.7 and the average of pos-test was 17.5, so the data was normal. In conclusion, the rubber cord elbow curl training affect the strength of shoulder and arm muscles volleyball extracurricular of male students of SMP Telekomunikasi Pekanbaru.Keywords: Rubber Cord Elbow Curlr, the strength of shoulder and arm muscles.